Organic matter composition and thermal maturity evaluation of Mesoproterozoic source rocks in the Beetaloo Sub-Basin, Australia. (December 2022) - Faiz, Mohinudeen; Altmann, Carl; Baruch, Elizabeth; Côté, Alexander; Gong, Se; Schinteie, Richard; Ranasinghe, Padmasiri
Highlights: A new formula to calculate vitrinite reflectance from alginite reflectance. Alginite reflectance correlated with H/C ratio of kerogen. Oil - gas windows for Proterozoic shales defined according to maturity parameters. Abstract: The Beetaloo Sub-basin in northern Australia comprises extensively developed marine, organic-rich shales within the Mesoproterozoic Velkerri and Kyalla formations. Oil and gas derived from the thermal maturation of primitive organic matter in these shales represent some of the oldest and best-preserved hydrocarbon accumulations identified worldwide. The organic matter is derived largely from prokaryotes with petrographic evidence indicating these primarily occur as filamentous strands or lamellae typical of cyanobacteria (blue-green algae) and commonly referred to as 'alginite'. The shales also contain bitumen generated through thermal maturation of the primary organic matter, as well as pyrobitumen remaining as a residue after secondary cracking of heavy hydrocarbons to gas. At present, no well-defined method exists to accurately assess thermal maturity nor define their hydrocarbon generation windows in source rocks of this age. Our organic petrographic and geochemical analyses indicate alginite reflectance (Ra ) increases with thermal maturity showing consistent relationships with depth, atomic H/C of kerogen and aromatic molecular ratios of extractable organic matter in the shales. Among the aromatic parameters tested, vitrinite reflectance calculated from methylphenanthrene index (MPI-1 Rc ) shows the strongest correlation with Ra (Rc = 0.5834Ra + 0.3842) confirming it is an effective parameter to calibrate thermal maturity models, particularly for wells where only organic petrology data are available. Molecular and isotopic composition of in situ hydrocarbons from two deep wells suggest the primary hydrocarbon generation window for Mesoproterozoic source rocks lies between Ra ∼ 0.2 % (Rc ∼ 0.5 %) and ∼ 1.5 % (Rc ∼ 1.25 %) with the dry gas threshold at Ra > 2.5 % (Rc > 1.8 %). These findings represent a refinement of the existing source rock maturity evaluation methods for the Beetaloo Sub-basin and serve as a guide for assessing other Precambrian petroleum systems worldwide.